INTERPERSONAL METAFUNCTION IN MORGAN FREEMAN’S SPEECH IN THE OPENING OF THE QATAR 2022 WORLD CUP - Ningrum, Dwi Kurnia Surya; Suriyani, Siti; Nurlela, Nurlela; Zein, T. Thyrhaya (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
This qualitative study conducts a discourse analysis of Morgan Freeman's speech at the Qatar 2022 World Cup Opening, focusing on the use of interpersonal metafunction. The research explores how Freeman's linguistic choices establish social relationships, convey attitudes, and reflect the social and cultural context of the event. The analysis reveals that Freeman predominantly utilized declarative clauses, creating a sense of unity and engagement with the audience. Additionally, a high percentage of modalizations of probability was observed, indicating his confidence in the success of the World Cup and the unifying power of sports. Freeman's linguistic choices also reflected his intention to promote inclusivity and foster a sense of belonging. Modulations of obligation and inclination further shaped the audience's perception and engagement, emphasizing invitation, encouragement, and inclusivity rather than strict commands or obligations. Freeman's language choices positioned him as an inclusive and engaging speaker, resonating with the diverse audience and reflecting the social and cultural context of the event. This study contributes to understanding how language influences social interactions and enhances audience engagement in a global setting.